Involvement of Bone or Neurovascular Structures by Soft Tissue Sarcoma at Mr Imaging as Prognostic Factors - Panicek, D. (Institutional Knowledge at Singapore Management University, 1997)
To determine if magnetic resonance (MR) imaging findings of soft-tissue sarcoma involving bone or neurovascular structures allow prediction of local recurrence, distant metastasis, or disease-specific survival. MATERIALS AND METHODS: Preoperative MR images of 46 patients with soft-tissue sarcoma were reviewed for tumor involving bone or major vessels or nerves. MR imaging findings were correlated with local recurrence, distant metastasis, and disease-specific survival after surgery and chemotherapy and/or radiation therapy. Primary tumors were predominantly in the lower extremity (n = 35 [76%]), deep (n = 44 [96%]), and high-grade (n = 35 [76%]). RESULTS: On MR images, bone invasion occurred in 12 patients (26%), major-vessel encasement in five patients (11%), and major-nerve encasement in seven patients (15%). In patients with (n = 12) and those without (n = 34) bone invasion, frequencies of disease-related death (in nine [75%] and 12 [35%] patients, respectively) were significantly different (P = .02); frequencies of local recurrence or distant metastasis were not significantly different. In patients with and those without major- vessel or major-nerve encasement, there were no significant differences between frequencies of local recurrence, distant metastasis, or disease- specific survival. CONCLUSION: In soft-tissue sarcoma, bone invasion on MR images was predictive of decreased disease-specific survival. MR imaging findings of bone or neurovascular involvement otherwise appear to be more important for tailoring surgery than for predicting local recurrence, distant metastasis, or survival.